2.5D, 3D and 4D printing in nanophotonics - a progress report. (2022) - Zhang, Wang; Wang, Hao; Wang, Hongtao; You En Chan, John; Ruan, Qifeng; Liu, Hailong; Yang, Joel K.W.
Abstract: Additive manufacturing produces 3D geometries by depositing material in a layer-by-layer fashion. Commonly, the resolution of additive manufacturing is in the millimeter and micrometer scales, due to limitations in mechanical precision and material properties. In the past two decades, nanoscale additive manufacturing has been achieved using femtosecond lasers that crosslink resin through a two-photon polymerization lithography (TPL) process. In this progress report, we present some of the recent efforts on nanoscale printing using TPL. We provide examples of nanoscale 2.5D, 3D and 4D printing by TPL and their corresponding applications in nanophotonics. We discuss the benefits of fabricating these geometries by the printing approach. Finally, we summarize the challenges and provide our perspective to improve the performance of nanoscale printing.